Investigations of the Activating Effect of Frothers and Organic Depressors Under Cationic Flotation - S. Titkov; T. Gurkova; N. Panteleeva; T. Chumakova; S. Aliferova; E. Konoplev; I. Michailova (International Mineral Processing Congress, 2003)
Cationic flotation using alkylamines and their derivatives as collectors, and characterized by high selectivity of mineral particle separation, is finding ever growing industrial application. In recent years the industrial application has been initiated of new cationic collectors - alkylmorpholines. Efficiency of cationic surfactants operation as collectors is dependent upon their colloid and sorption properties and the availability of silicate .carbonate rock-forming mineral impurities in the ore, which sorb the cationic collector. Investigations have been carried out on the influence of frothers and organic depressors with various compositions upon physical-chemical and flotation properties of alkylamines and alkylmorpholines. On the basis of these investigations requirements for organic depressor were developed and new flotation reagents were proposed (V-1 frother and KS-MF depressor). The use of new reagents enables one to decrease considerably the consumption of expensive cationic collectors and to enhance the floatability of coarse mineral particles. Data of new reagents industrial application is presented. The reagents developed can be used for flotation processing of other ores.